(untitled) - David Nunan (Cambridge, New York, 1988)
The book presents curriculum theory and practice as these are applied to English language teaching. The concept of "learner-centredness" provides a unifying theme for the work as a whole. It takes as its starting point what is done by language teachers in their classes. The concept of a negotiated model is developed, in which the curriculum is arrived at collaboratively between teachers and learners
Keywords: curriculum planning,english language - study and teaching - foreign speakers